1996
DOI: 10.1557/proc-424-425
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Mechanisms and Vacuum Requirements for Fed Phosphors

Abstract: Degradation of phosphors in field emission displays (FED's) is described and related to electron beam stimulated surface reactions between ZnS and residual gas in the vacuum system. The requirements for producing and maintaining vacuums in FED packages is reviewed and limitations associated with the size of the FED's are discussed. It is concluded that vacuum production and maintenance is critical to the performance of FED's, and this is not a simple task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 5 publications
3
31
0
Order By: Relevance
“…The FEDs have a much lower power consumption and are more compact than CRTs, while offering better viewing angles and faster video refresh rates than AMLCDs. 1 Manufacturing of FEDs is also easier than AMLCDs and, combined with the drive in the consumer market towards low-power portable electronic devices, these flat panel displays are set to become an important future contender in the display market.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FEDs have a much lower power consumption and are more compact than CRTs, while offering better viewing angles and faster video refresh rates than AMLCDs. 1 Manufacturing of FEDs is also easier than AMLCDs and, combined with the drive in the consumer market towards low-power portable electronic devices, these flat panel displays are set to become an important future contender in the display market.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the decrease in CL intensity is not only influenced by the ZnO layer thickness. Swart et al 1 suggest that surface reactions alone do not decrease the CL intensity, but that point defects created beneath the oxide layer during oxide formation may also increase the probability of radiationless relaxation and the subsequent decrease in CL intensity. The XPS data indeed showed that, although a 11 nm ZnO layer formed during the degradation process, oxygen was incorporated in the ZnS up to a depth of 30 nm.…”
mentioning
confidence: 99%
“…In this case, a non-luminescent oxide layer, which is known to reduce the CL intensity of the CRT/FED phosphors, may form on the surface. For examples, it was demonstrated that when zinc sulfide (ZnS) based phosphors were exposed to a prolonged irradiation by energetic beam of electrons, the ZnS host dissociated into reactive ionic Zn 2+ and S 2-species, which in turn combined with ambient vacuum gases such as O 2 and H 2 O to form non-luminescent ZnO or ZnSO 4 layers or H 2 S gas (Swart el al., 1998;Itoh et al, 1989) as explained by the ESSCR model (Holloway et al, 1996(Holloway et al, , 2000. In the case of oxide based systems, the electron beam induced dissociation of atomic species is followed by desorption of oxygen from the surface.…”
Section: Cathodoluminescence Intensity Degradationmentioning
confidence: 99%
“…It was demonstrated that when these phosphors were irradiated with the beam of electrons for a long period of time they lose their CL intensity and this occured simultaneously with desorption of oxygen (O) from the phosphor surfaces. In the process, an oxygen deficient non-luminescent layer was formed on the surface whose formation could be explained by an electron stimulated surface chemical reaction (ESSCR) model proposed by Holloway and co-workers (Holloway et al, 1996(Holloway et al, , 2000. The desorption of atomic species was explained by Knotek-Fiebelman electron stimulated desorption (ESD) proposed by Knotek and Feibelman (Knotek and Feibelman, 1978).…”
Section: Introductionmentioning
confidence: 96%
“…Electron-stimulated chemical reactions between the phosphor and constituents of the residual atmosphere in vacuum (H 2 , CO, CO 2 , H 2 O) are another potential Coulomb aging mechanism. Typical values for Coulomb aging when the luminance decreases to half its initial value are 100-200 C/cm 2 [34]. The dwell time is the time that the electron beam spends to excite the phosphor.…”
Section: Phosphors and Phosphor Plate Fabricationmentioning
confidence: 99%